We knew you had it in you - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Promoting Farmer Innovation. Harnessing Local Environmental Knowledge in East Africa. SIDA-RELMA and UNDP copublication. 1999. 133 pp. US$ 10 10.40 (Payable to DOS VU Amsterdam) Resource Development Unit CDCS. De Boelelaan 1115 1085 HV Amsterd